Crack tip plasticity in dynamic fracture - Mataga, P.A.; Freund, L.B.; Hutchinson, J.W. (The Journal of physics and chemistry of solids, 1987)
The mechanics of crack tip plasticity in dynamic crack growth is considered as it influences two modes of dynamic fracture—cleavage and micro-void nucleation, growth and coalescence. The subject is approached using both the continuum theory of visco-plasticity and dislocation dynamics. The viewpoint underlying each approach is that the crack is traveling through material with a relatively high density of pre-existing mobile dislocations. Analysis is directed at discovering the role played by the associated rate-dependent plasticity in establishing conditions for dynamic crack propagation. The theory is far from complete, but the contents of the paper should serve to aid understanding of basic material fracture phenomena, such as cleavability and the ductile-brittle transition, as well as provide a background for the engineering theory of dynamic fracture.